Pengembangan Video Pembelajaran Sejarah - Syafri Naldo; Wahidul Basri (Jurnal Kronologi, 2021)
AbstractThis research is motivated by the lack of use of learning media in the history learning process. The purpose of this study is to produce learning media, namely history learning videos so that the learning process is more interesting and not boring. The method in this research is R&D (Research and Development). The development model in this study is the ADDIE model, namely, Analysis, Design, Development, Implementation and Evaluation. Due to time and cost limitations, this research only reached the ADDI stage, namely, Analysis, Design, Development and Implementation. The subject of this research is class XI IPS 1 SMA N 1 Lunang. Meanwhile, the feasibility and practicality of this product were tested by history learning material experts and history learning media experts, history subject teachers and students using a questionnaire. The result of the feasibility of learning materials by history learning material experts is 3.6 with a very feasible category. The result of the feasibility of learning media in terms of history learning media by history learning media experts is 3.5 with a very decent category. The practicality test of the media by the teacher is 3.5 with a very practical category. The media test for students is 3.5 with a very practical category. Therefore, the historical learning video media about maritime kingdoms in the archipelago with a Hindu-Buddhist pattern is very feasible and practical to be applied in learning history at school.Keywords: Learning Video Media, History LearningAbstrakPenelitian ini dilatarbelakangi dengan kurangnya penggunaan media pembelajaran dalam proses pembelajaran sejarah. Tujuan penelitian ini adalah untuk menghasilkan media pembelajaran yaitu video pembelajaran sejarah supaya proses pembelajaran lebih menarik dan tidak membosankan. Metode dalam penelitian ini adalah R&D (Research and Development). Model pengembangan dalam penelitian ini adalah model ADDIE yaitu, Analisis,Design, Development, Implementasi dan Evaluasi. dikarnakan keterbatasan waktu dan biaya maka penelitian ini hanya sampai pada tahap ADDI yaitu,Analisis,Design,Development dan Implementasi. Subjek penelitian ini yaitu kelas XI IPS 1 SMA N 1 Lunang. Sedangkan kelayakan dan kepraktisan produk ini diuji oleh ahli materi pembelajaran sejarah dan ahli media pembelajaran sejarah, guru mata pelajaran sejarah dan peserta didik dengan mengguakan angket. Hasil kelayakan materi pembelajaran oleh ahli materi pembelajaran sejarah adalah 3.6 dengan kategori sangat layak. Hasil kelayakan media pembelajaran dari segi media pembelajaran sejarah oleh ahli media pembelajaran sejarah adalah 3.5 dengan kategori sangat layak. Uji praktikalitas media oleh guru adalah 3.5 dengan kategori sangat praktis. Uji coba media kepada siswa adlah sebesar 3.5 dengan kategori sangat praktis. Maka dari itu media video pembelajaran sejarah tentang kerajaan maritim di nusantara yang bercorak hindu buddha sangat layak dan praktis diterapkan dalam pembelajaran sejarah di sekolah. Kata Kunci: Media Video Pembelajaran, Pembelajaran Sejarah